Subprimal type and quality grade affect fatty acid composition and cooked firmness of ground beef patties - C. M. Garner; John A. Unruh; Melvin C. Hunt; Elizabeth A.E. Boyle; Terry A. Houser; Sally L. Stroda (Kansas Agricultural Experiment Station Research Reports, 2014)
Subprimals can be stored in a vacuum package for extended periods of time at low storage temperatures. The number of days that subprimals may be held before processing can be influenced by the distribution chain, accessibility, and subprimal price fluctuations. Extended vacuum storage before grinding could affect biochemical, oxidative, and microbial properties of these subprimals and influence sensory properties. Our objective was to determine the effects of two subprimal types (chuck roll and knuckle), two quality grades (Premium Choice and Select), and three vacuum-packaged storage aging times before processing (7, 21, and 42 days) on ground beef patty sensory properties.
Keywords: Cattlemen& #x27; s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen& #x27; s Day; Beef; Ground beef; Subprimal types; Quality grades; Vacuum storage; Sensory properties